Constitutional Change: Towards Better Human Rights Protection in Australia - Mohammad Ibrahim (The Constitutional Court of the Republic of Indonesia, 2019)
Many legal scholars contend that Australia does not have a charter of rights in its Constitution. The legal scholar Rosalind Dixon, however, suggests that the Constitution does include some provisions that could be viewed as resembling a (partial) bill of rights. This constitutional framework might cause one to ponder whether human rights are adequately protected in the Australian constitutional system. This paper attempts to consider this question. It is argued that the protection of human rights under the Constitution, federal and state laws is not fully capable of responding to at least three human rights crises presented. Accordingly, the paper suggests that Australia should consider the idea of amending the Constitution in order to better human rights protection in the country. It offers suggestion that the Canadian model protection of human rights could be considered as one of the primary sources for reforms in the future.